AI-Supported Practical Learning in Vocational Education: Challenges and Design Principles - Yunda Michel Rismawati; Nunung Setiawati; Erik Yumita Sudharta; Putu Sudira Fajaryati; Pipit Utami; Yoga Sahria (Utan Kayu Publishing, 2025)
Artificial intelligence (AI) is increasingly integrated into vocational education to support practical skill development and technology-enhanced training environments. However, existing studies remain fragmented across different technological applications and provide limited conceptual understanding of how AI technologies collectively support practical learning processes. This study conducts a systematic literature review following the PRISMA 2020 guideline to synthesize current evidence on AI-supported practical learning in vocational education. Seventeen studies published between 2018 and 2025 were identified from the Scopus database and analyzed through thematic synthesis. The findings indicate that AI technologies are commonly implemented through simulation platforms, intelligent tutoring systems, learning analytics and performance monitoring tools, adaptive learning systems, and AI-supported experiential learning environments. Five recurring pedagogical mechanisms were identified: simulation-based practice, intelligent skill guidance, performance feedback and analytics, adaptive learning pathways, and experiential or work-based learning. The review also highlights implementation challenges related to infrastructure, data availability, ethical concerns, and teacher AI literacy. Based on these findings, a conceptual framework is proposed to explain how AI technologies support practical learning and competency development in vocational education. The synthesis also suggests opportunities for integrating emerging approaches such as multimodal learning analytics and facial expression recognition (FER) to better understand learner engagement during practical training activities.